Proses Bermigrasi Dan Kondisi Sosial Ekonomi Migran Suku Banten di Kelurahan Kaliawi Bandar Lampung - Chintya Mutiara Dewi; Trisnaningsih Trisnaningsih; Sugeng Widodo (JPG (Jurnal Penelitian Geografi), 2019)
This study aims to find out the process of migrating and the socio-economic condition of Bantenese migrants in Kaliawi Village Bandar Lampung City. The method used was descriptive quantitative analysis. The 110 families were selected through propotional random sampling technique. The data collection technique was done through interview, documentation and questionnaire. Data analysis used percentage and scoring. The results of this study were: 1. The migration process was easy due to several reason the lack of job opportunities in the place of origin (80.78%). Travel migrating Banten tribes to Kaliawi Village was easy (69.23%). The purpose of migrating improved the standard of living (69.23%). The source of information migrating was information from friends (82.7%). 2. Socio-economic conditions was low (61.54%). The education level of the heads of migrant was low (90.38%). The type of migrants job was trader (63.46%), Migrant income was low (69.23%). Ownership of valuables owned by migrants was low ( 61.54%).Penelitian ini bertujuan mengetahui proses bermigrasi dan kondisi sosial ekonomi migran Suku Banten di Kelurahan Kaliawi Bandar Lampung. Metode yang digunakan deskriptif analisis kuantitaif. Populasi 110 KK dengan teknik propotional random sampling Pengambilan data dengan wawancara, dokumentasi dan kuisioner. Analisis data menggunakan presentase dan scoring. Hasil penelitian ini : 1. Proses bermigrasi mudah meliputi: Alasan Suku Banten migrasi ke Provinsi Lampung kurangnya kesempatan kerja di daerah asal (80,78%). Perjalanan bermigrasi Suku Banten ke Kelurahan Kaliawi mudah (69,23%). Tujuan bermigrasi memperbaiki taraf hidup (69,23%). Sumber informasi bermigrasi adalah informasi dari teman (82,7%). 2. Kondisi Sosial ekonomi rendah (61,54%) meliputi tingkat pendidikan kepala keluarga migran rendah (90,38%). Jenis pekerjaan migran pedagang (63,46%). Pendapatan migran rendah (69,23%). Kepemilikan barang berharga yang dimiliki migran rendah (61,54%).Kata kunci: migran, migrasi, sosial-ekonomi